Effect of the granulometry and proportions of maize and cassava flours on the techno-functional and sensory properties of composite couscous-like product - Awah Noella; Panyo’o Akdowa Emmanuel; Nguimbou Richard Marcel (Applied Food Research, 2025)
This study aimed to evaluate the impact of granulometry and the proportions of maize and cassava flours on the techno-functional and sensory attributes of a composite granulated couscous-like product. Twelve types of couscous-like products were produced from maize and cassava flours in varying proportions, based on household practices and couscous standards. The dry couscous-like product had low lipid content, suitable moisture content, and acceptable grain size, but low homogeneity. The incorporation of cassava flour and an increase in fineness increased the whiteness, starch content, cooking loss, weight gain, volume gain indices, and swelling index. However, cooking time decreased as the proportion of cassava flour increased. An agglomerative hierarchical clustering analysis revealed four significantly different couscous-like samples, with the most preferred being the 25INImaiz+75INIcass, which consisted of 25 % maize flour, a fine fraction of 30.38 %, a medium fraction of 50.47 %, and a coarse fraction of 19.18 %, and 75 % cassava flour. The couscous-like product prepared with cassava flour was preferred for its appearance, mouthfeel, taste, aroma, and appreciable proximate and techno-functional properties.